Ennakkotietoja herneen ja virnan säilyvyydestä seosviljoissa Suomessa - Hänninen, P. (Agricultural and Food Science, 1949)
In the investigation the author has collected results, already published, concerning the survival of peas and vetches in mixed crops in Finland, and supplemented them with results of his own field experiments (Table 1). In addition to these, observations in different parts of the country have been made (Fig. 1). Results have shown that the pea varieties used have not survived in the southern part of Finland as well as in the middle and northern part of the country. In southern Finland vetch has given better results than peas. Better survival of pea varieties (Artturi, Sinikka and Thursday II) in more northern places has been explained as being due to the difference in the length of the day. Some Swedish results seem to corroborate this opinion (2).